Preparation techniques for transmission electron microscopy of Hydra - Holstein, Thomas W.; Hess, Michael W.; Salvenmoser, Willi (Electron microscopy of model systems, 2010)
Hydra is a classical model organism in developmental and cell biology with a simple body plan reminiscent of a gastrula with one body axis and a limited number of cell types. This rather simple organism exhibits a regeneration capacity that is unique among all eumetazoans and is largely dependent on the stem cell properties of its epithelial stem cell population. Molecular work in the past few years has revealed an unexpected genetic complexity of these simple animals, making them an interesting model for studying the generation of animal form and regeneration. In addition, Hydra has an interstitial stem cell system with a unique population of nematocytes, neuronal cells that are characterized by an explosive exocytotic discharge. Here, we compare classical and modern transmission electron microscopy (TEM) fixation protocols including protocols for TEM immunocytochemistry (post-embedding immunogold labeling). We presume that TEM studies will become an important tool to analyze cell-cell interactions as well as cell matrix interrelationships in Hydra in the future.